IMPORT PENETRATION, FOREIGN DIRECT INVESTMENT, AND NON-OIL EXPORT DYNAMICS IN NIGERIA: A LONGITUDINAL ANALYSIS (1981–2012) - Abdullahi , Aisha Halima; Eze, Chukwudi Nnamdi (Ayden Journal of Management and Social Sciences, 2025)
Since the 1970s, Nigeria's economy has been heavily reliant on crude oil, leading to the neglect of other sectors, particularly agriculture. This overdependence on oil has left the economy vulnerable to fluctuations in international crude oil prices and underscored the need for diversification. Calls for economic diversification have grown louder over the years, emphasizing the potential benefits of developing the non-oil sector. This review examines Nigeria's economic landscape, tracing the evolution of its dependence on oil and the resultant neglect of other sectors. It highlights the imperative of diversifying the economy to mitigate risks associated with oil price volatility and unlock the untapped potential of non-oil sectors.